The Moderating Effect of Occupational Burn-Out on the Link of Career Competencies to Career Sustainability Amid the COVID-19 Pandemic: A Mixed-Method Study - Zhang, Wei; Chin, Tachia; Peng, Jian-Ben; Shan, Yi-Nan; Agbanyo, George Kwame (Frontiers in Psychology, 2022)
Due to the Covid-19 pandemic most employees face increasing career-related stress, particularly those who work in multinational corporations (MNCs), because the international travel constraints prevent them from going back to their families. Hence, it is imperative to investigate the critical impact of employees’ occupational burnout (OB) on career-related outcomes. In response, this research explores the moderating effect of OB on the relationships between career competences (CCs) and career sustainability (CS). To achieve a more comprehensive understanding of relevant issues, we adopted a mixed-method research design including both qualitative and quantitative analysis. Findings indicate that all three dimensions of CCs (i.e., reflective, communicative and behavioral career competencies; RC, CC, and BC) were positively related to CS; moreover, OB negatively moderated the individual relationships of CC and BC with CS. The main contribution of this study is to enrich the existing career literature by addressing the critical moderating role of OB in the links of CC and BC individually with CS. Practical implications are also discussed in this study.